Riset Ilmiah Kelautan Berdasarkan UNCLOS 1982 dan Perkembangannya di Indonesia - Artiasha, Kisti (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
The United Nations Convention Law of The Sea (UNCLOS) 1982 has provided rules for conducting marine scientific research activities at the international level. This is intended so that there are limits in terms of exploiting marine wealth for the benefit of mankind. Sophisticated technological capabilities of developed countries can be a gap to gain more advantages from countries that do not yet have advanced technology in marine scientific research. The research method used is normative juridical which refers to the approach of international conventions or legislation. The problem that will be discussed in this article is regarding how to regulate marine scientific research activities and technology transfer based on UNCLOS 1982 and its development in Indonesia.Keywords; Marine scientific research; UNCLOS1982; regulatory developments in Indonesia.